The Role of Financial Literacy and Credit Card Debt in the Brazilian Consumer - Donadio, Rosimara (2012)
This paper aims to revise the literature on the influence of credit card access and level of financial literacy over the indebtedness of the Brazilian consumer. The indebtedness of the Brazilian population is growing, and most of these debts come from credit cards. Many factors influence the growing indebtedness: low level of financial literacy, the dissemination of credit cards as well as the way they simplify transactions, and the growing offer of credit, among others. These and other factors seem to be contributing to the increase in Brazilian consumers expenses and indebtedness, leading to serious individual, social, and economic consequences.